Performance of Steel-Jacketed RC columns using various cementitious materials - Mostafa, Saadeldin Mostafa Saadeldin Mohamed (AUC Knowledge Fountain, 2019)
Repair and strengthening techniques of RC elements are considered to be challenging due to time, cost, and space constraints. Conventionally, several techniques have been used in the retrofitting of RC element. These techniques includes epoxy repair, concrete and steel jacketing and FRP. Recently a new technique has been introduced which is concrete filled steel jackets. Although the previously mentioned techniques have been thoroughly studied, little research has been found in this area. Consequently, more data is required towards a safe and efficient design of this technique. In this work, a strengthening technique for RC columns is proposed, which is concrete filled steel jackets. This technique comprises a steel cage consisting of four steel angles with steel strips at fixed spacing to prevent the buckling of the angles. The space between the RC column and the steel cage is filled with different classes of concrete. The experimental program consisted of ten RC columns, two of which are unstrengthened columns. Eight steel cages were used with the same length of the column to confine the RC columns. Four different concrete mixes of filling concrete were prepared with different grades to be used as the filling concrete. No interface or shear connectors were used between the old and new filling concrete. LVDT's and strain gauges were mounted on the specimens to record the load displacement and stress strain curves of the specimens. The properties of hardened concrete mixes were assessed using the cube strength at 28 days. The specimens were then uniaxially loaded until failure. Afterwards, the results of jacketed specimens were compared to each other as well as control specimens i.e. specimens without jacketing. In order to address the effect of the composite jacketing, the strength of the columns are to be compared with the Eurocode 4 and Regalado design equations for composite sections. The results of this study reveal that the proposed technique have significant effects on the capacity, ductility and stiffness of the strengthened columns for different types of filling concrete. Also, this technique is more effective and economic for lower strength filling concrete as it behaves as a composite section. Moreover, the Eurocode 4 design equations tends to overestimate the capacities of the columns and Regalado's equation provide reasonable design values. For future work, it is recommended to examine wider set of concrete mixtures to confirm the findings of this study, the bond between concrete and steel should be thoroughly studied and observe the change in the confinement action on the RC columns and compare the performance of the jacket under eccentric and lateral loads with the results of this study